Performance Audit of Employees State Insurance Corporation (ESIC 2008-2013) - CAG of India (CAG of India, 2014)
"This Report contains the result of Performance audit of Employees’ State Insurance Corporation (ESIC) for the period 2008-09 to 2012-13. This performance audit of the ESIC was conducted to assess whether: (i) financial management and governance was efficient; (ii) mechanism for coverage of new establishments was effective; (iii) implementation of scheme, including procurement of medicines/ equipment's was efficient and effective, benefits provided to insured persons/ beneficiaries were as per norms; and (iv) infrastructure development was effective and as per norms. The Instances mentioned in this report are those, which came to notice in the course of test audit conducted during the period 2013-14 as well as those which came to notice in earlier years, but could not be reported in previous Audit Reports; matters relating to the period subsequent to 2012-13 have also been included, wherever necessary."
For the Period 2008-09 to 2012-13